2019
DOI: 10.1073/pnas.1900870116
|View full text |Cite|
|
Sign up to set email alerts
|

Multiple modes of convergent adaptation in the spread of glyphosate-resistant Amaranthus tuberculatus

Abstract: SignificanceWhile evolution has been thought of as playing out over millions of years, adaptation to new environments can occur very rapidly, presenting us with key opportunities to understand evolutionary dynamics. One of the most amazing examples of real-time evolution comes from agriculture, where due to the intense use of a few herbicides, many plant species have evolved herbicide resistance to become aggressive weeds. An important question has been whether herbicide resistance arises only rarely and then … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
147
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(150 citation statements)
references
References 64 publications
(89 reference statements)
3
147
0
Order By: Relevance
“…Evolutionary rescue has been explored theoretically (e.g., Gomulkiewicz and Holt, 1995;Uecker and Hermisson, 2016;Anciaux et al, 2018) and observed repeatedly in both experiments (e.g., Bell and Gonzalez, 2009;Lindsey et al, 2013;Ramsayer et al, 2013) and in host-pathogen systems in nature (e.,g., Wei et al, 1995;Feder et al, 2016). More recently, a number of studies have used genetic data to suggest that evolutionary rescue has occurred in the wild, including crickets becoming song-less to avoid parasitoid flies (Pascoal et al, 2018, reviewed in McDermott, 2019, killifish deleting receptors to tolerate pollution (Oziolor et al, 2019), hares moulting brown instead of white to avoid predation in snowless winters (Jones et al, 2018), bats altering hibernation to survive white-nose syndrome (Gignoux-Wolfsohn et al, 2018), and tall waterhemp evolving herbicide resistance (Kreiner et al, 2019). In nearly all of these cases there is strong evidence of a recent selective sweep by a very beneficial allele.…”
Section: Discussionmentioning
confidence: 99%
“…Evolutionary rescue has been explored theoretically (e.g., Gomulkiewicz and Holt, 1995;Uecker and Hermisson, 2016;Anciaux et al, 2018) and observed repeatedly in both experiments (e.g., Bell and Gonzalez, 2009;Lindsey et al, 2013;Ramsayer et al, 2013) and in host-pathogen systems in nature (e.,g., Wei et al, 1995;Feder et al, 2016). More recently, a number of studies have used genetic data to suggest that evolutionary rescue has occurred in the wild, including crickets becoming song-less to avoid parasitoid flies (Pascoal et al, 2018, reviewed in McDermott, 2019, killifish deleting receptors to tolerate pollution (Oziolor et al, 2019), hares moulting brown instead of white to avoid predation in snowless winters (Jones et al, 2018), bats altering hibernation to survive white-nose syndrome (Gignoux-Wolfsohn et al, 2018), and tall waterhemp evolving herbicide resistance (Kreiner et al, 2019). In nearly all of these cases there is strong evidence of a recent selective sweep by a very beneficial allele.…”
Section: Discussionmentioning
confidence: 99%
“…Short-read, shotgun sequence data at a depth of~10X were generated from 23 male and 19 female A. tuberculatus plants from Illinois as part of an ecological study to better understand A. tuberculatus population structure (Kreiner et al 2018). The sequence reads produced by this protocol were 150-bp pairedend reads with an approximate insert length of 300 bp.…”
Section: In Silico Marker Testingmentioning
confidence: 99%
“…Scott.) and Eleusine indica (L.) Gaertn . The next steps for the consortia will be to not only produce genomes for the identified priority weed species but to revisit and improve the genomes of weed species whose initial drafts were produced with earlier generation sequencing technology, are fragmented, are incomplete or are not presented as chromosome‐scale scaffolds.…”
Section: Introductionmentioning
confidence: 99%